Development and application of wire-mesh sensors for high-speed multiphase flow imaging - Santos, Eduardo Nunes dos (2015)
Multiphase flows are present not only in nature but also are very common in industrial activities such as in exploration, production and transport of oil and gas. In oil production, the mixture of gas, oil and water is often found streaming through production columns and flow risers. A lot of progress has been made in recent years in the development and application of measurement techniques applied to multiphase flow measurement in order to accurately quantify, predict and control the flow of multiphase mixtures. Especially, high-speed imaging of multiphase flows has received much attention in recent years. Wire-mesh sensors are flow-imaging devices and allow the investigation of multiphase flows with high spatial and temporal resolution. In the past, such sensors have found widespread application in gas-liquid flows. Its operating principle is based on measurement of a single electrical property (conductivity or permittivity) of flowing mixture. The objective of this work is the application of the wire-mesh technique for high-speed multiphase flow imaging in different flow conditions as applied so far, as well as the further development of this technique by adding the capability of dual-modality (simultaneous conductive/capacitive) operation. Hence, novel routines and data processing algorithms for the investigation of two-phase flows of the type gas-liquid and solid-liquid (slurry) were developed and tested. As a step towards the further development of the wire-mesh sensor technique, a novel dual- modality electronics being able to simultaneously evaluate the conductivity and permittivity component of a fluid through vector measurements (amplitude and phase) is introduced. Further, a model-based algorithm to fuse the data of dual-modality wire xi mesh sensor is developed to obtain individual phase fraction distributions in gas-oil- water three-phase flows. Hence, this thesis’ main contribution to the field of flow measurement and investigation is the development and application of software solutions for extracting flow parameters from wire-mesh sensor data, as well as the improvement in the hardware of measuring electronics. As a result, the range of application of wire-mesh sensors is enhanced being capable to investigate two-phase gas-liquid and slurry flows as well as gas-liquid-liquid three-phase flow problems through high-speed flow imaging.